2020
DOI: 10.3390/jcm9051479
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Natural Compounds in the Medical Treatment of Uterine Fibroids

Abstract: Uterine fibroids (UFs) remain a significant health issue for many women, with a disproportionate impact on women of color, likely due to both genetic and environmental factors. The prevalence of UFs is estimated to be approximately 70% depending on population. UF-derived clinical symptoms include pelvic pain, excessive uterine bleeding, gastrointestinal and voiding problems, as well as impaired fertility. Nowadays numerous methods of UF treatment are available—from conservative treatment to invasive surgeries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 233 publications
(303 reference statements)
1
34
0
Order By: Relevance
“…The annual costs attributed to UFs range between $5.9 and $34.4 billion per year in the United States alone and hundreds of billions worldwide [ 86 ]. Although UFs are benign tumors, they can cause a myriad of symptoms and outcomes, including pelvic pain, abnormal uterine bleeding, bladder dysfunction, and even infertility [ 87 ]. Despite the high morbidity and cost associated with UFs, the exact pathophysiology is not completely delineated [ 88 ], yet there are theories and reports of associated risk factors.…”
Section: Uterine Fibroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The annual costs attributed to UFs range between $5.9 and $34.4 billion per year in the United States alone and hundreds of billions worldwide [ 86 ]. Although UFs are benign tumors, they can cause a myriad of symptoms and outcomes, including pelvic pain, abnormal uterine bleeding, bladder dysfunction, and even infertility [ 87 ]. Despite the high morbidity and cost associated with UFs, the exact pathophysiology is not completely delineated [ 88 ], yet there are theories and reports of associated risk factors.…”
Section: Uterine Fibroidsmentioning
confidence: 99%
“…The authors found that Alba and Romina cultivars presented the best results: they decreased collagen 1A1, fibronectin, versican, and activin A mRNA expression in UF cells [ 112 ]. In vitro studies have shown that curcumin, which is abundantly found in turmeric, prevents fibroid growth as it inhibits UF cell proliferation by regulating the apoptotic pathway [ 87 ]. Isoliquiritigenin, which is abundantly found in liquorice, and soybean have been reported to induce growth inhibition and apoptosis of UF cells [ 114 ].…”
Section: Uterine Fibroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usage of plant products such as leaf, bark, fruits, roots, etc. is a very common practice since ancient time in the field of medicine 9,[39][40][41][42][43][44][45][46][47] .…”
Section: Sperm Motility Test and Viability Testmentioning
confidence: 99%
“…Nonetheless, there is still no significant clinic evidence available so far. Therefore, it is highly recommended to obtain more clinical trials utilizing these compounds before endorsing widespread usage [5].…”
Section: Introductionmentioning
confidence: 99%